The Effect Of Instructional Design Of English Subject Based On Component Display Theory On Student’s Achievement - Mulyadi, Mulyadi (2011)

(untitled)
This study constitutes an attempt to apply the Component Display Theory (CDT) as a knowledge base on designing written instruction. It aims to investigate the effect of “secondary presentation” on; (1) students’ overall achievement, (2) the six learning targets: remember concept, remember procedure, remember principle or rule, and use concept, use procedure, use principle, (3) each level of performance of remember and use simultaneously.